2007
DOI: 10.1002/14651858.cd002818.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine for fatigue in multiple sclerosis

Abstract: Cochrane Database of Systematic Reviews REFERENCES References to studies included in this review CMSRG 1987 {published data only} * The Canadian MS Research Group. A randomized controlled trial of amantadine in fatigue associated with multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(70 citation statements)
references
References 44 publications
1
64
0
5
Order By: Relevance
“…116 In a more recent study, amantadine was compared to modafinil and acetyl-L-carnitine, as well as placebo. 117 The study demonstrated some benefit of amantadine over the other treatment arms at the one month assessment of MFIS score.…”
Section: Treatment Of Fatiguementioning
confidence: 99%
“…116 In a more recent study, amantadine was compared to modafinil and acetyl-L-carnitine, as well as placebo. 117 The study demonstrated some benefit of amantadine over the other treatment arms at the one month assessment of MFIS score.…”
Section: Treatment Of Fatiguementioning
confidence: 99%
“…In addition, evidence of the efficacy of antifatigue medications in patients with MS is mixed, suggesting that exclusion of subjects on antifatigue medication may not have biased the sample much. 39,40 The subjects in this study all noted fatigue as a significant symptom despite a wide range of disability, yet it is not known whether subjects on antifatigue medication would have reacted in a similar manner. Future studies could examine the effect of intermittent exercise on individuals with MS who are taking antifatigue medication.…”
Section: Discussionmentioning
confidence: 87%
“…Changes to circadian rhythms through lack of routine and disrupted sleep-wake patterns also perpetuate fatigue. 14 Currently, no approved medical treatment is available for MS-related fatigue in Germany, 15 and drug trials to date suggest poor efficacy. 16 However, behavioral treatment approaches have shown encouraging effects.…”
Section: Patient Interviews/focus Groupmentioning
confidence: 99%